Inovasi Penataan Pedagang Kaki Lima di Kabupaten Maros - Pauzi, Rizal; Tikson, Deddy T.; Hasniati, Hasniati (Departemen Ilmu Administrasi FISIP UNHAS, 2021)
The Innovation Structuring of street vendors In Maros regency (supervised by Deddy T. Tikson and Hasniati). This study aims to analyze the results of innovation structuring of street vendors in Maros Regency based on the criteria of the United Nations (UN). This research was conducted in Culinary Area of ​​No Wave Beach of Maros Regency. The method used in this study is a qualitative approach with a focus on innovation results from the arrangement of street vendors in Maros regency. There is also a research design used is case study (case study). The result of the research shows that the innovation of street vendors in Maros Regency based on criterion of United Nations (UN) is less successful. This was because of the 6 indicators, 1 indicator that partnership is not met because there was no professional cooperation either government, private or banking. 4 less effective indicators that sustainability was not working well because there was no special regulation governing culinary areas, innovation indicators in local and transferable contexts did not provide specific publications related to secondary data as well as special information related to street vendors in the area of ​​culinary beaches and non- other areas were still difficult to adopt the concept in applied. Indicators of gender equality and social exclusion because they had not demonstrated traditional special food and local wisdom in the arrangement of street hawkers, although gender and local wisdom were not contradictory and indicators of leadership and community empowerment due to governor commitment were not accompanied by clear policies and lack of merchant empowerment concepts a clear five foot post relocation. The indicators that become the strength of this innovation was the impact. Impact indicators provide benefits for both street vendors, government and the environment.